Jewish women - Brod, Max (2020)
The only English translation of the novel by Max Brod, the close friend and publisher of Franz Kafka. Jewish Women was first published in German in 1911 and was an immediate success. The novel portrays the lives of prosperous families of the assimilated Jewish community of Prague shortly before WW1. It is set in the spa town of Teplitz and explores the thoughts and feeling of young middle-class Jewish women who are largely undereducated and obliged to rely for their future happiness on making a suitable marriage. It was written at a time when both the author and the characters he depicts were poignantly unaware of the trauma and tragedy that would be visited upon the Jewish community in the decades to come.